PENGARUH KOMUNIKASI DAN PROMOSI PEMASARAN TERHADAP KEPUASAN KONSUMEN PADA PT. MINERAL MEDAN - ERNI WAHYUNI (JURNAL ILMIAH KOHESI, 2021)
Marketing communication carried out such as sponsorship, advertising, through events or events, print media, online media,direct marketing to prospective consumers and other activities that can improve marketing has not been able to increaseconsumer satisfaction so it is necessary to look for other strategies that can increase consumer satisfaction. Promotion is theinteraction between individuals, face-to-face shown to create, improve, master, or maintain a mutually beneficial exchangerelationship with another party. - William J. Stanton. Increasingly fierce competition occurs in the processing of bottled drinksbecause this product is the most needed daily requirement by the community. It is not easy to be the best, in addition tohaving to provide the best quality there are also factors of consumer behavior patterns that are not easy to guess. As for howto get feedback with a purchase loyalty survey, then the customer complaint or dissatisfaction can be immediately taken anddetermined the best solution by the company.